47.3k views
2 votes
Expand (5x – 3y + 2) using identity.​

User Aremmell
by
4.5k points

1 Answer

5 votes

Answer:


(5x - 3y + 2)^2=25x^2+9y^2+4-30xy-12y+20x

Explanation:

We need to expand (5x – 3y + 2)² using identity.

Using identity,


(a+b+c)^2=a^2+b^2+c^2+2ab+2bc+2ac

We have, a = 5x, b = -3y and c = 2

So,


(5x - 3y + 2)^2=(5x)^2+(-3y)^2+2^2+2(5x)(-3y)+2(-3y)(2)+2(2)(5x)\\\\=25x^2+9y^2+4-30xy-12y+20x

So, the required answer is
25x^2+9y^2+4-30xy-12y+20x.

User Ayyappa Boligala
by
5.0k points